Desenvolvimento da criança e educação infantil: simbolização, gênese e produção subjetiva - Zanluchi, Stelen Paula (2020)
In recent years, intense research work has contributed to the revision and strengthening of references for pedagogical practices in the field of early childhood education. There is still an important work to be done towards the constitution of educational practices that promote childhood development. The present study was willing to study the infant ontogenesis beyond a cognitive and unidimensional bias, understanding it as the structuring of a complex psychophysiological synthesis of biological-cultural nature, proposing the following problem: which symbolic resources (participations, interactions, speeches, languages, materials, etc.) are constituted in the learning situations provided to young children in early childhood education and how do such resources propel their development? The objective was to investigate the way in which the symbolic and emotional interactions and connections offered to children have the potential to constitute themselves or not in development situations, as well as the impact of the practices organized in these environments on the experience of young children. The need to study such an impact is based on the growing phenomenon of early childhood education as a central environment for childhood experience, thus assuming anthropological functions of cultural transmission and education of new subjects. The study was based on a qualitative exploratory research, which data generation was carried out with two groups of children between two and three years of age and their teacher. The observation of the video recorded material allowed the composition of the events that, by representativeness or exceptionality, better expressed the semantic contents conveyed in the interactions between teacher and children, followed by the microgenetic analysis of these events. Supported by the theoretical assumptions of Vygotski (2010; 2002a; 2002b; 2002c; 2002d), González Rey (1999; 2000; 2006; 2010; 2013) and Bleichmar (1994; 2010; 2005a; 2005b), the ontogenetic constitution process was understood as anchored by the mediation of exogenous, symbolic and cultural movements, concomitantly supported by emotional and subjective processes, through which the child productively appropriates what is provided by the environment. The study revealed the existence of a profound duplicity that cuts across the constitution of the field of interactions and organization of practices in early childhood education. On the one hand, obstacles were found linked to the objectification of the child: constraint of the space-time of child participation; inhibition of the space-time of imaginary appropriation and the exercise of playing; imposition of dissonant practices with child development; schooling tendency of interactions; field of emotional receptivity of interactions hampered in the sense of operations sensitive to the emotional, communicational demands and the search for emotional contact of children; camouflaged or covert ties that favor some children over others; semantic contents that convey a strong control over the bodies, subjectivities, communications and psychic and emotional productions of children. On the other hand, the production of an interactive field with a responsive capacity, of emotional and symbolic sensitivity to the individual and collective demands of the children, demonstrated to act as a constituent of interactions and consonant practices and appropriate to the experiences of young children, being a fundamental factor for the constitution of children an interpsychological bond in collective environments. Some of the urgencies in the field unfold from these findings: consolidate continuing education processes that develop studies based on situated pedagogical practices and studies of the child and its ontogenesis; constitute studies on the field of symbolic-emotional processes since the initial training, aiming to provide theoretical and methodological resources to future teachers so that they intervene in order to overcome situations of subjection imposed on children, among others. In this way, early childhood education appears as a fundamental environment for guaranteeing more equitable conditions for development, education and child protection, and as a community that contributes to expectations about childhood and its rights.